Doctrine of Trinity Based on Qur’anic and Biblical Studies - Ahmad Hermawan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2018)
The Journal discuss on the problem of Trinity as a doctrine that underlies Christian faith. Trinity is a delusion theological doctrine which is ambiguous and enforced. Al-Qur’an criticize the confusion of trinity as a doctrinal astray of human invention which has no basis teaching from Allah’s which has triggered conflicts within the Christian body itself. Through the method on historical criticism that is based on Qur’anic studies and the Biblical studies the confusion of Trinitarian doctrine is revealed in two aspects both are Political aspects, and the deviation of the source of religious teachings. The political interests of the Roman Emperor Constantine in strengthening the influence of his power proved to influence the formulation of the doctrine of the trinity at the Council of Nicaea 325 C.E. The influence of Roman power in the doctrine was the inclusion of the teachings of polytheism and paganism in the dogma of the Trinitarian faith which confused the elements of monotheism and polytheism. The distortion of religious teachings in the doctrine of the trinity is the absence of the teaching of Jesus Christ in the Gospel that teaches worship on him except the call to monotheism. The doctrine of the divinity of Jesus comes from Paul's teachings that deviate from the teachings of monotheism colored by the influence of Hellenism philosophy. Consequently, there was conflict in the body of Christian schools about the concept of Trinity to the present day.